THE RESCUE. TAKING RAPID DECISIONS WITH A NARROW MARGIN OF ERROR (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
Based on the analysis of a real life event, this paper tries to recreate the act of making a decision just as if the event took place today and decisions were to be made for the future. Decisions imply a minimum rationality and an "ex ante" process, that is to say, always turned towards the future.The fact reported and analyzed is the search and rescue of a professional mountaineer who was considered missing in the Andes Mountains at almost 7000 masl.The particularity of making decisions in this case is that time is a supercritical variable, the margin of error of decisions is small and decreases rapidly over time.What tools and concepts can be combined when one must decide quickly with a lot of information and multiple variables at hand?The study of this search and rescue process allows the analysis of decision-making processes applying protocols and decision trees and its evolution in relation to urgency. Thus, it is possible to identify and understand the use of key concepts for companies in periods of crisis that demand rapid decisions in complex contexts with a large amount of information.
Keywords: Decision; protocol; margin of error; vulnerability